Student Drama Production as an Implementation of Experiential Learning in Higher Education - Afsun Aulia Nirmala; Tri Mulyono (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
The implementation of student-centered learning in higher education requires learning models that provide authentic experiences and support the development of twenty-first-century competencies. One of the approaches that fulfills these objectives is Experiential Learning, which emphasizes learning through direct experience, reflection, conceptualization, and active experimentation. This study aims to examine the implementation of Experiential Learning through student drama production and to investigate its contribution to the development of students’ academic and social competencies. The study employed a mixed-methods approach with an explanatory sequential design. The participants were 40 students of the Indonesian Language and Literature Education Study Program at Universitas Pancasakti Tegal who were enrolled in the Drama course during the 2025/2026 academic year. Quantitative data were collected through questionnaires and analyzed using descriptive statistics, while qualitative data were obtained through participant observation, semi-structured interviews, and documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that Experiential Learning was effectively implemented through the stages of drama production, including script selection, role assignment, rehearsals, performance, and evaluation. All participants perceived the learning model as effective, with 70% rating it as very effective and 30% as effective. Furthermore, the implementation of Experiential Learning contributed to the development of communication, collaboration, creativity, critical thinking, problem-solving, leadership, and adaptability skills. The study concludes that student drama production serves as an effective experiential learning model that promotes meaningful, authentic, and competency-based learning in higher education.